Pelatihan Ecoprint untuk Mengembangkan Kreativitas Peserta Didik di SDN 2 Setu Wetan - Irma Rahmawati; Isqi Zanzabila; Kharisma Fitria Yustiani; Khoerunissa; Kholid; Asih Wahyuningsih; Nita Fauziyah (Jurnal Pengabdian Masyarakat Indonesia (JPMI), 2025)
The ecoprint training was motivated by the difficulties experienced by SDN 2 Setu Wetan students in creative learning. In this context, ecoprint training can be a solution as an effective method to develop the creativity skills of SDN 2 Setu Wetan students. In addition, this service activity aims to provide direct experience of processing wet leaves and flowers into a useful product through ecoprint as a form of developing the creativity of SDN 2 Setu Wetan students. This activity was held on February 10-12, 2025, involving 181 participants consisting of students in grades 4, 5 and 6 of SDN 2 Setu Wetan. The ecoprint training service is carried out through 4 stages, namely the socialization stage, the material delivery stage, the activity implementation stage and the last program evaluation. The method used in ecoprint training activities is to provide a demonstration of how to do ecoprint by using leaves and flowers into a product in the form of a tablecloth. The result of this activity is that SDN 2 Setu Wetan students have skills in making handicraft products through ecoprint. Then from this service, it can be concluded that ecoprint training not only develops creativity and innovation skills but can also increase collaboration between students. Keywords: Ecoprint, Creativity, Students